Gains from Diversification - Hadar, Josef; Russell, William R.; Seo, Tae Kun (Review of Economic Studies, 1977)
Josef Hadar, William R. Russell, Tae Kun Seo; Gains from Diversification, The Review of Economic Studies, Volume 44, Issue 2, 1 June 1977, Pages 363–368, h